Quercetin ameliorates chromium toxicity through improvement in photosynthetic activity, antioxidative defense system; and suppressed oxidative stress in Trigonella corniculata L. - Aslam, Muhammad Ashfaq; Ahmed, Shakil; Saleem, Muhammad; Shah, Anis Ali; Shah, Adnan Noor; Tanveer, Mohsin; Ali, Hayssam M.; Ghareeb, Rehab Y.; Hasan, Mohammad E.; Khan, Jallat (Frontiers in Plant Science, 2022)
Trigonella corniculata L. (fenugreek) a high yield crop also termed “Kasuri methi” is extensively used for many decades due to its diet, nutrition, and remedial characteristics. Kasur city is famous for its cultivation. During Cr-mediated irrigation T. corniculata accumulate a higher magnitude of heavy metals due to its natural verdant vegetative growth. Heavy metal Cr is a non-essential component that is absorbed by the plants causes toxicity in the form of inhibited vegetal progression, ultrastructure alterations, interfering mineral nutrition, disturbance in photosynthetic and respiratory processes, leaf chlorophyll damage, enzyme retardation, oxidative injury, yield decrease and vegetal demise. Its biomagnification inside individuals is highly lethal due to its carcinogenic nature. It is therefore prerequisite to frame certain strategies to alleviate the detrimental effects of Cr heavy metals toxicity through application of suitable stress ameliorants. In this regard, the present trial was carried by applying 100 ml of K2Cr2O7 solution into each pot except control (C) to assess its impacts on growth and other distribution in T. corniculata. To alleviate Cr generated stress different treatments of Quercetin hydrate i.e., Q1 (15uM), Q2 (25uM), and Q3 (40uM) were used as a stress ameliorant through seed priming. Concentration treatments of Q remained influential regarding distressing different plant physiological and chemical characteristics as well as growth and biomass under the heavy metal stress. Results revealed that toxic heavy metal contaminant (Cr) negatively affected plant growth showing a reduction in root and shoot mass, chlorophyll content, plant height, enzymatic activity. Cr also affected the nutritional content of plant seeds having low fiber, ash, moisture, carbohydrate, protein, fats, and flavonoid contents. However, application of quercetin stress ameliorant resulted in a significant increase in root and shoot length and mass, chlorophyll content, plant height, photosynthesis, transpiration, enzymatic activity and seed nutritional quality as compared to contaminant (Cr) counterparts in T. corniculata. Among different applied treatments having chromium contamination Q2.Cr exhibit the most signified trial outcomes representing as a plant stress ameliorant under heavy metal stress.